Fine tuning a logical model of cancer cells to predict drug synergies: combining manual curation and automated parameterization - Flobak, Åsmund; Zobolas, John; Vazquez, Miguel; Steigedal, Tonje S.; Thommesen, Liv; Grislingås, Asle; Niederdorfer, Barbara; Folkesson, Evelina; Kuiper, Martin (Frontiers in Systems Biology, 2023)
ÅF: Devised the project and developed the main conceptual ideas. Designed and developed prototype for simulation pipeline. Developed and implemented drug response combination simulation software. Analysed drug response prediction data and model performance. Designed and executed cell line experiments. Manually curated drug combination response data. Designed and executed xenograft experiment. Supervised drug combination matrix experiments. Supervised tissue microarray experiments. JZ: Developed and implemented production-ready drug response combination simulation software. Executed various simulations, analysed drug response prediction data and model performance, produced resulting figures, produced supplementary information, produced github repositories, made all analyses reproducible. MV: Analysed drug combination data. Developed and implemented drug response combination simulation software. TS: Supervised xenograft experiments. LT: Supervised xenograft experiments. AG: Prepared and analysed tissue microarrays of xenograft tumours. BN: Manually curated drug combination response data. Designed and executed drug combination matrix experiments. EF: Manually curated drug combination response data. Designed and executed drug combination matrix experiments. MK: Analysed drug response prediction data and model performance. Supervised the project.